The relationship between structural characteristics of long-term care institutions and their initial operating budgets - Wang, Xiaojing; Coyte, Peter C. (Frontiers in Public Health, 2025)
PurposeIn the context of a rapidly aging population, this study focuses on an important issue concerning long-term care institutions, attempting to explore the relationship between structural characteristics and initial operating budgets.MethodsData analysis was performed based on 581 long-term care institutions collected from the Shanghai Municipal Civil Affairs Bureau. Statistical analyses were conducted using IBM SPSS Statistics 24.0 with the PROCESS macro (version 3.5) for moderation analyses and Stata 16.0 for endogeneity tests.ResultsThe analyses revealed a significant U-shaped relationship between the gross floor areas of long-term care institutions and their initial operating budgets. Industry competition negatively moderated the effect of gross floor area on initial operating budget and also significantly exerted a direct negative effect on budgets. In addition, staffing arrangement showed a positive effect on initial operating budgets. Ownership type mattered: publicly constructed institutions had significantly lower initial operating budget compared to privately constructed institutions, whereas publicly operated institutions were associated with significantly higher initial operating budgets than privately operated ones. Institutions with leased property reported lower initial operating budgets than those with self-owned property.ConclusionThis study demonstrates that the initial operating budgets of long-term care institutions are significantly associated with their structural characteristics.